2020
DOI: 10.3329/ajmbr.v6i2.48050
|View full text |Cite
|
Sign up to set email alerts
|

Moringa leaf extract as a bio-stimulant on growth, yield and nutritional improvement in cabbage

Abstract: Moringa is a valuable plant whose leaves are enriched with antioxidants, amino acids, vitamins and mineral nutrients and can be used as a bio-stimulant. A field work was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University (BAU), Mymensingh, during rabi season from November 2017 to February 2018 in order to investigate the effect of moringa leaf extract (MLE) on growth, yield and nutrient status of cabbage. The experiment was laid out in a randomized complete block design with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
(7 reference statements)
3
9
0
Order By: Relevance
“…The highest dry weight of root (29.00 g) was recorded in T 4 treatment which was statistically similar with T 3 and the lowest dry root weight was obtained from control (17.39 g). These results are in agreement with the findings of Muhamman et al (2013), Ozobia, (2014, Rady et al (2015), Rana et al (2019), Yusuff and Abiola, (2019) and Hoque et al (2020) who reported increased plant height, fresh weight and dry weight of shoot and better crop growth rate in different vegetable crops including tomato, eggplant, common bean, cauliflower, cucumber and cabbage respectively with foliar application of MLE compared to control. T 1 =Control (foliar spray with water), T 2 = MLE sprayed at 2 weeks after transplanting, T 3 =MLE sprayed at 2 weeks and 4 weeks after transplanting, T 4 =MLE sprayed at 2 weeks after transplanting and after every two weeks thereafter…”
Section: Effect Of Mle On Growth Parameters Of Brinjalsupporting
confidence: 92%
See 2 more Smart Citations
“…The highest dry weight of root (29.00 g) was recorded in T 4 treatment which was statistically similar with T 3 and the lowest dry root weight was obtained from control (17.39 g). These results are in agreement with the findings of Muhamman et al (2013), Ozobia, (2014, Rady et al (2015), Rana et al (2019), Yusuff and Abiola, (2019) and Hoque et al (2020) who reported increased plant height, fresh weight and dry weight of shoot and better crop growth rate in different vegetable crops including tomato, eggplant, common bean, cauliflower, cucumber and cabbage respectively with foliar application of MLE compared to control. T 1 =Control (foliar spray with water), T 2 = MLE sprayed at 2 weeks after transplanting, T 3 =MLE sprayed at 2 weeks and 4 weeks after transplanting, T 4 =MLE sprayed at 2 weeks after transplanting and after every two weeks thereafter…”
Section: Effect Of Mle On Growth Parameters Of Brinjalsupporting
confidence: 92%
“…The results of our study were accorded to those of several comparable studies of some researchers (Sivakumar and Ponnusami, 2011;Abdalla and EI-Khoshiban, 2012) suggesting that the increased uptake and accumulation of some macronutrient elements such as N, P, K and S in several plants under investigation as a consequence of application of moringa leaf extract. Hoque et al (2020) also found increased N, P, K and S contents in cabbage head due to application of MLE. Merwad (2017) found the highest percent increase of N, P, and K accumulation in pea for shoot and for seed with foliar application of 4% MLE.…”
Section: Figure 1 Percent Increase In Fruit Yield Of Brinjal Over Control As Influenced By Different Treatmentsmentioning
confidence: 67%
See 1 more Smart Citation
“…Modern agricultural production aims to provide sustainable management practices that are eco-friendly and low cost. In recent years, the natural plant growth enhancer is the main focus of study for many researchers around the globe (1). Moringa (Moringa oleifera L.) leaves are used as green manure and as a potential natural growth stimulant (2).…”
Section: Introductionmentioning
confidence: 99%
“…The leaf extract of moringa leaves (MLE) was used as bio-stimulant of growth. The exogenous application of MLE efficiently increased the uptake of different macronutrients (N, P, K, and S) and increased plant growth and development (Hoque et al 2020) and mitigates salt-induced adversities (Merwad 2018).…”
Section: Introductionmentioning
confidence: 99%